The Permeability of the Sodium Channel to Organic Cations in Myelinated Nerve - Hille, Bertil (The Rockefeller University Press, 1971)
The relative permeability of sodium channels to 21 organic cations was studied in myelinated nerve fibers. Ionic currents under voltage-clamp conditions were measured in sodium-free solutions containing the test cation. The measured reversal potential and the Goldman equation were used to calculate relative permeabilities. The permeability sequence was: sodium ≈ hydroxylamine > hydrazine > ammonium ≈ formamidine ≈ guanidine ≈ hydroxyguanidine > aminoguanididine >> methylamine. The cations of the following compounds were not measurably permeant: N-methylhydroxylamine, methylhydrazine, methylamine, methylguanidine, acetamidine, dimethylamine, tetramethylammonium, tetraethylammonium, ethanolamine, choline, tris(hydroxymethyl)amino methane, imidazole, biguanide, and triaminoguanidine. Thus methyl and methylene groups render cations impermeant. The results can be explained on geometrical grounds by assuming that the sodium channel is an oxygen-lined pore about 3 A by 5 A in cross-section. One pair of oxygens is assumed to be an ionized carboxylic acid. Methyl and amino groups are wider than the 3 A width of the channel. Nevertheless, cations containing amino groups can slide through the channel by making hydrogen bonds to the oxygens. However, methyl groups, being unable to form hydrogen bonds, are too wide to pass through.